2016
DOI: 10.2147/jmdh.s103881
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of e-health technology by physicians: a scoping review

Abstract: ObjectiveThe goal of this scoping review was to summarize the current literature identifying barriers and opportunities that facilitate adoption of e-health technology by physicians.DesignScoping review.SettingMEDLINE, EMBASE, and PsycINFO databases as provided by Ovid were searched from their inception to July 2015. Studies captured by the search strategy were screened by two reviewers and included if the focus was on barriers and facilitators of e-health technology adoption by physicians.ResultsFull-text scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 67 publications
5
116
0
2
Order By: Relevance
“…Other important issues highlighted in previous studies are the lack of electronic skills among patients and providers, which perhaps also nurtures (cultural) resistance in using eHealth tools [49,50]. This seems unfortunate as a positive attitude and perception among physicians could play an important role in making home telehealth services more acceptable for the elderly population [51].…”
Section: Discussionmentioning
confidence: 99%
“…Other important issues highlighted in previous studies are the lack of electronic skills among patients and providers, which perhaps also nurtures (cultural) resistance in using eHealth tools [49,50]. This seems unfortunate as a positive attitude and perception among physicians could play an important role in making home telehealth services more acceptable for the elderly population [51].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, worldwide studies have been completed and have described the use of telemedicine in palliative care (Collier et al, ; Hoek, Schers, Bronkhorst, Vissers, & Hasselaar, ; van Gurp, van Selm, van Leeuwen, Vissers, & Hasselaar, ; van Gurp, van Selm, Vissers, van Leeuwen, & Hasselaar, ). According to de Grood et al, to ensure the effective uptake of e‐Health technologies, physicians perspectives' need to be considered when creating an environment that enables the adoption of e‐Health in health care (de Grood, Raissi, Kwon, & Santana, ). Cost and liability issues, and an un‐willingness to use e‐Health technology were the most mentioned barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Cost and liability issues, and an un‐willingness to use e‐Health technology were the most mentioned barriers. Furthermore, training and support were seen to facilitate the adoption of e‐Health technology among healthcare professionals (de Grood et al, ). Similar to this, Kruse et al, found, in their systematic review which included ( n = 30) articles, that barriers to adoption of telemedicine worldwide, were technically challenged staff and a resistance to change among the healthcare professionals (Scott Kruse et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although DHTs hold significant promise for the improvement of various elements of behavioral health intervention, and surveys have indicated that people with SMI are enthusiastic about using technology [19,20], adoption has been slow, testing of outcomes from acceptability to effectiveness has been limited, and codified development and deployment strategies have been lacking [21][22][23][24][25][26][27][28]. These preliminary efforts need to be undertaken before their effectiveness can be tested and verified so that the resulting findings can be incorporated into the redesign and reconfiguration of DHTs to provide an optimal solution.…”
Section: The Potential Of Digital Health Tools For Psychiatric Practicementioning
confidence: 99%